PEMBERDAYAAN KADER DALAM PENANGANAN HENTI JANTUNG DI DESA GHEO GHOMA KECAMATAN ENDE UTARA KABUPATEN ENDE - Sekunda, Maria Salestina; Rifatunnisa; owa, khrispina (Poltekkes Kemenkes Kupang, 2024)
The role of cadres is very important in efforts to anticipate and handle hypertension complications such as cardiac arrest. One of the roles of cadres when the elderly experience cardiac arrest is that cadres are able to prevent and treat cardiac arrest by providing basic life support and are able to give advice to the elderly to avoid things that can be at risk of causing sudden death. The Community Service activity was held on May 1-2, 2024 in the Gheoghoma Village office hall and was attended by 11 village cadres and the Head of Gheo Ghoma Village. The method used is education and skills to do basic life support. At the beginning of the activity, a test of cadre knowledge about basic life support was carried out and then simulations and demonstrations were carried out and then closed with a post test. From the results of the activity, data was obtained that most of the cadres had understood and were able to provide basic life support, as evidenced by the results of the answers to the questions given where the respondents had less knowledge than 75% and in the post stage after being given material and demonstrations on the treatment of cardiac arrest, the results of the increase in respondents' knowledge about basic life support were obtained, which was as much as 83%. In addition, in training activities, cadres are able to carry out basic life support using BHD phamptom aids and obtain a score from 0% to 75%. Therefore, it is highly expected that the village management will continue to cooperate with the government, especially the cadres in improving knowledge and other skills in preventing sudden death in the community by conducting continuous training so as to increase knowledge and skills that will have an impact on the prevention and handling of sudden death due to cardiac arrest